Resurrection of the octocorallian genus Antillogorgia for Caribbean species previously assigned to Pseudopterogorgia, and a taxonomic assessment of the relationship of these genera with Leptogorgia (Cnidaria, Anthozoa, Gorgoniidae) - Williams, Gary C.; Chen, Jei-Ying (Zootaxa, 2012)
The genus Antillogorgia Bayer, 1951 is resurrected for species of zooxanthellate, pinnately-branched gorgonians with sc-lerite complements that include well-developed scaphoids, and inhabit coral reefs of the western Atlantic, particularlyfrom the Bahamas through the Caribbean. These species were previously assigned to the Indo-Pacific genus Pseu-dopterogorgia Kükenthal, 1919 by Bayer, 1958 (thus making Antillogorgia a junior synonym of Pseudopterogorgia), butare shown here to warrant generic separation. Both morphological as well as molecular evidence is provided to justify distinguishing the two genera. Taxonomic relationships to a third gorgoniid genus, Leptogorgia, are also discussed.